Three Siblings with Prader-Willi Syndrome: Brief Review of Sleep and Prader-Willi Syndrome - Arina Bingeliene; Colin M. Shapiro; Sharon A. Chung (Case Reports in Neurological Medicine)
Prader-Willi syndrome (PWS) is a genetic disorder characterized by short stature, mental retardation, hypotonia, functionally deficient gonads, and uncontrolled appetite leading to extreme obesity at an early age. Patients with this condition require multidisciplinary medical care, which facilitates a significant improvement in quality of life. PWS is the first human disorder to be attributed to genomic imprinting. Prevalence varies in the literature, ranging from 1 in 8,000 in the Swedish population to 1 in 54,000 in the United Kingdom. Rarely, the genetic mechanism responsible for Prader-Willi syndrome can be inherited. We report a highly unique case of three siblings who share this condition. This report describes a case of two brothers and one half sister with PWS. All three siblings have sleep-related complaints. The sister died at the age of 24 years in her sleep, with the cause of death reported as obstructive sleep apnea. The outcome was positive in both of the brothers’ cases as a result of professional medical care and specific tailored recommendations implemented by their mother. A review of the relevant literature vis-à-vis sleep and PWS is provided.